SENDER AND RECEIVER BASED EFFICIENT BROADCASTING ALGORITHM IN MOBILE AD HOC NETWORK (MANET) - Maheswari.R, Uma; B, Chithra. (IJRDO -Journal of Computer Science Engineering, 2016)
In mobile ad hoc networks(MANETs), all the nodes in the networkoverhear every data transmission occurringin its vicinity and thus, consumes energyunnecessarily. This paper proposed a NovelBroadcast Algorithms for mobile ad hocnetworks to improve the effectiveness andafford guarantee for complete delivery ofbroadcasting. An important objective is todecrease relay redundancy and to evade thebroadcast storm difficulty. It proposes twobroadcasting algorithms they are, Senderbased algorithm and Receiver basedalgorithm. In this paper we proposed a newSender based algorithm selects subset offorwarding nodes using 1-hop neighborinformation. The proposed algorithmsimprove the efficiency and also guaranteefull delivery.